Cell cycle arrest and apoptotic studies of Terminalia chebula against MCF-7 breast cancer cell line: an in vitro and in silico approach - Reddy, Pruthvish; Pradeep, Sushma; S. M., Gopinath; Dharmashekar, Chandan; G., Disha; M. R., Sai Chakith; Srinivasa, Chandrashekar; Shati, Ali A.; Alfaifi, Mohammad Y.; Elbehairi, Serag Eldin I.; Achar, Raghu Ram; Silina, Ekaterina; et al. (Frontiers in Oncology, 2023)
Breast cancer is the second greatest cause of mortality for women worldwide and one of the most prevalent malignant diseases. Radiotherapy and chemotherapy used to treat various types of cancers may cause certain side effects. Medicinal extracts and compounds derived from certain plants are also being investigated for potential anti-cancer properties and are expected to have fewer side effects. The anti-proliferative and apoptogenic effects of Terminalia chebula fruit (TCF) extract on breast cancer, MCF7 cell lines, have been examined in the current study. Epidermal Growth Factor Receptor (EGFR) are known to regulate a wide range of biological processes, including cell growth, differentiation, proliferation, and cell death by delivering extracellular signals upon activation. Hence, these receptors were considered to assess the anticancer efficacy of various TCF phytocompounds. The results of the Molecular Docking studies indicate that saccharopine demonstrated a higher binding affinity of -9.7 kcal/mol with EGFR compared to the reference compound (17β-Estradiol: -4.4 kcal/mol). The subsequent Molecular Dynamics Simulation (MDS) and binding energy calculation analyses suggested stable binding patterns and conformation of the EGFR-saccharopine complex under simulation. To demonstrate this phytochemical's safety and promise as a targeted therapy in the field of oncology, more study is needed to isolate it and test it in vivo for anticancer efficacy.